Comparing the efficacy and safety of the Skyflow device with those of the Solitaire FR stent in patients with acute ischemic stroke: a prospective, multicenter, randomized, non-inferiority clinical trial. (2nd December 2021) - Zhou, Tengfei; Li, Tianxiao; Zhu, Liangfu; Li, Zhaoshuo; Li, Qiang; Bai, Wei-xing; He, Ying-kun; Liu, Xiao; Guan, Haitao; Long, Youming; Liu, Jinchao; Wei, Liping; et al.
Abstract : Background: Mechanical thrombectomy is the standard treatment for acute ischemic stroke (AIS) with large vessel occlusion (LVO) in the anterior circulation. This trial aimed to indicate whether Skyflow, a new thrombectomy device, could achieve the same safety and efficacy as Solitaire FR in the treatment of AIS. Methods: This study was a prospective, multicenter, randomized, single blind, parallel, positive controlled, non-inferiority clinical trial. Patients with intracranial anterior circulation LVO within 8 hours from onset were included to receive thrombectomy treatment with either the Skyflow or Solitaire FR stent retriever. The primary endpoint was the rate of successful reperfusion (modified Treatment In Cerebral Infarction (mTICI) ≥2b) after the operation. The safety endpoints were the rate of symptomatic intracranial hemorrhage (sICH) and subarachnoid hemorrhage (SAH) at 24 hours after operation. Results: A total of 95 and 97 patients were involved in the Skyflow group and Solitaire FR group, respectively. A successful reperfusion (mTICI ≥2b) was finally achieved in 84 (88.4%) patients in the Skyflow group and 80 (82.5%) patients in the Solitaire FR group. Skyflow was non-inferior to Solitaire FR in regard to the primary outcome, with the criterion of a non-inferiority margin of 12.5% (p=0.0002) after being adjusted for the combined center effect and the National Institutes of Health Stroke Scale (NIHSS) score. The rate of periprocedural sICH and SAH did not differ significantly between the two groups. Conclusion: Endovascular thrombectomy with the Skyflow stent retriever was non-inferior to Solitaire FR with regard to successful reperfusion in AIS due to LVO (with a pre-specified non-inferiority margin of 12.5%).